Neuro, cardio, and reno protective activities of rosuvastatin in streptozotocin-induced type 2 diabetic rats undergoing treatment with metformin and glimepiride - Shailaja Rondi; Ramu Peddolla; Raj Kumar Venisetty (Wolters Kluwer Medknow Publications, 2014)
Diabetes is associated with complications like neuropathy, nephropathy, cardiomyopathy, and retinopathy due to increased oxidative stress and serum lipids. In the present study, rosuvastatin, a HMG-CoA inhibitor, was investigated for its protective effect in neuropathy, nephropathy, and cardiomyopathy based on the lipid-lowering property along with its pleiotropic effects such as improved blood flow to the organ and antioxidant defense. Type 2 diabetes was induced in Wistar rats by single i.p. administration of streptozotocin (50 mg/kg). These diabetic rats were treated with daily doses of rosuvastatin (10 mg/kg) alone, metformin (120 mg/kg) and glimepiride (1 mg/kg) and rosuvastatin in combination with metformin (120 mg/kg) and glimepiride (1 mg/kg) for a period of 6 weeks. The biochemical parameters involved in neuropathy, renopathy, and cardiopathy were estimated. Treatment resulted in significant (P < 0.05) decrease in thiobarbituric acid reactive substances (TBARS) and increase in levels of glutathione peroxidise and catalase in brain and kidney homogenates. Significant (P < 0.05) increase in high-density lipoproteins and decrease in creatinine kinase, triglycerides, total serum cholesterol represents the cardioprotective action, whereas significant (P < 0.05) increase in the latency in the hotplate model shows the neuroprotective activity, and significant (P < 0.05) decrease in blood urea nitrogen, creatinine levels and increase in serum total protein levels suggested the renoprotective actions. The unique properties of rosuvastatin such as antioxidant defense and lipid-lowering nature might have resulted in cardio, neuro, and renoprotective activity in type 2 diabetic rats treated with metformin and glimepiride.